SOCIAL IMPLICATIONS OF EARTHQUAKES ON THE WORK ETHIC OF TRADERS AT MANONDA PRESIDENTIAL MARKET, HAMMER CITY - Abdul Hakim; Nisbah; Jamaluddin (Tadulako Social Science and Humaniora Journal, 2023)
This study aims to investigate the work ethic of traders in public markets after experiencing the socioeconomic impacts of the earthquake. The social implications of the earthquake include the capabilities that arise in response to the impact of the earthquake, the adaptability to the challenges faced, and the dynamics in the social relations of traders.The results of this study reveal facts that explain the social implications of the earthquake on the work ethic of traders in the Inpres Manonda Market, Palu City. After experiencing the impact of the earthquake; 1) the traders created a social environment and production activities as a unity of functions in the m anagement of the trading business 2) strengthening work orientation with the belief that work is a gift from Allah SWT, 3) applying the principle of flexibility in the use of capital, 4) each trader gave strength to the construction of group roles as a safeguard from price pressures and competition.